ANALISIS KEMAMPUAN GURU DALAM MENGINTEGRASIKAN MATERI AJAR DENGAN KEBUTUHAN BELAJAR PESERTA DIDIK DI SEKOLAH DASAR - Julianti Putri; Rabiudin; Agus Yudiawan (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This study analyzes teachers' ability to integrate Indonesian teaching materials with the learning needs of fifth-grade students at MI Quba Kota Sorong. The research utilized a qualitative method with a phenomenological approach, conducted from April 22 to July 15, 2024, using observation, interview, and documentation techniques. Data were validated using source triangulation and coding techniques, while data analysis was performed using a qualitative descriptive approach. The results reveal several challenges teachers face in integrating Indonesian teaching materials with students' learning needs, including frequent curriculum changes that reduce teachers' focus on teaching, limited instructional time, ineffective learning strategies, a lack of reading materials for students, and the need for intensive and continuous teacher training. These factors hinder the integration process. Proposed solutions include conducting regular curriculum evaluations to achieve effective teaching with a focus on core materials. The use of read- aloud techniques can help with time management and maintaining student focus. Additionally, findings show that students prefer learning activities that involve games, songs, and pictures, which could serve as a foundation for Indonesian language teaching strategies at MI Quba Kota Sorong. This study recommends providing additional reading facilities and recruiting more teachers to ensure that each subject is taught by a dedicated teacher. The use of the SMART Goals method can help set specific and achievable learning objectives. These findings provide an overview for other SD/MI institutions to streamline their curriculum so that teaching materials better meet students' learning needs.